Pengaruh Brisk Walking Exercise terhadap Tekanan Darah pada Pasien Hipertensi - Anak Agung Sayu Risma Kusuma Dewi; V.M. Endang S.P. Rahayu; I Gusti Ayu Ari Rasdini; I Dewa Putu Gede Putra Yasa (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
Hypertension is called the Silent Killer which is the leading cause of asymptomatic death. Around 1.13 billion people in the world have hypertension, which means 1 in 3 people in the world have hypertension. The number of hypertensive patients continues to increase every year, it is estimated that in 2025 there will be around 1.5 billion people who have hypertension. One of the efforts to reduce blood pressure in hypertensive patients is to do brisk walking exercises which is a type of aerobic exercise, namely moderate activity using brisk walking techniques for 30 minutes with an average speed of 4 km/hour which is done 4 times a week. The purpose of this study was to determine the effect of brisk walking exercise on blood pressure in hypertensive patients at Puskesmas I North Denpasar in 2022. The type of research used was quasi-experimental using a nonequivalent control group design. The sampling technique used is probability sampling with simple random sampling, namely 34 respondents (17 intervention groups and 17 control groups). The results of the Wilcoxon test for changes in systolic and diastolic blood pressure in the intervention group obtained p-value = 0.000 and 0.001 0.05. The results of the Mann-Whitney difference test obtained p values = 0.000 and 0.004 so that it can be concluded that there is an effect of brisk walking exercise on blood pressure in hypertensive patients. Therefore, it is expected to do brisk walking exercise regularly to reduce blood pressure in hypertensive patients.